2018
DOI: 10.1103/physrevb.97.094201
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance in organic semiconductors: Including pair correlations in the kinetic equations for hopping transport

Abstract: We derive the kinetic equations for polaron hopping in organics that explicitly take into account the double occupation possibility and pair intersite correlations. The equations include simplified phenomenological spin dynamics and provide a self-consistent framework for the description of the bipolaron mechanism of the organic magnetoresistance. At low applied voltages the equations can be reduced to effective resistor network that generalizes the Miller-Abrahams network and includes the effect of spin relax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 31 publications
3
19
0
1
Order By: Relevance
“…This phenomenon is closely related to intersite correlations [14,20,21]. It reappears in the conventional theory when at least pair correlations in close sites are taken into account [14]. The similar mechanism of magnetoresistance was also proposed for ordinary semiconductors [22] but to the best of the author knowledge was never observed in non-organic materials.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…This phenomenon is closely related to intersite correlations [14,20,21]. It reappears in the conventional theory when at least pair correlations in close sites are taken into account [14]. The similar mechanism of magnetoresistance was also proposed for ordinary semiconductors [22] but to the best of the author knowledge was never observed in non-organic materials.…”
Section: Introductionmentioning
confidence: 59%
“…To simplify the numeric calculations we excluded from calculations all hops with distance longer than a(ξ c + 3)/2 and all the sites with |ε i | > (ξ c + 3)T . We solved the system of equations (10), (12), (14) in three approximations: in the Miller-Abrahams approximation (MA), in the approximation when pair correlations up to the distance 2r c are taken into account (we denote it as "cor1" approximation) and in the approximation when correlation up to the third order and distance r c are calculated ("cor2" approximation). The results are averaged over ten disorder configurations.…”
Section: A Correlations In the Mott Law Regimementioning
confidence: 99%
“…It can also take place, for example, when the electrons and holes are injected into the QDs not optically, but electrically. It is known that in organic semiconductors the hyperfine and exchange interaction lead to electron and hole spin correlations even at room temperature, which can be evidenced in magnetoresistance [48][49][50] and modification of the total PL intensity [51,52] in small magnetic fields. Since optical orientation is very inefficient in organic semiconductors, the dynamic spin polarization may be a useful tool for spin initialization.…”
Section: B Numerical Resultsmentioning
confidence: 99%
“…By contrast, in the strong magnetic field, the electron spin precession frequency equals to Larmor frequency which is the same for all hopping sites, so the spin relaxation gets suppressed [15]. Recently, some of us have shown that OMAR can be related to the nonequilibrium electron spin correlations [16,17], which appear due to the applied voltage. The relaxation of these correlations leads to OMAR.…”
Section: Introductionmentioning
confidence: 99%